Risk Factors for Postoperative Venous Thromboembolic Complications after Microsurgical Breast Reconstruction - Sultan, Steven M.; Jackson, Danielle S.; Erhard, Heather A.; Greenspun, David T.; Benacquista, Teresa; Garfein, Evan S.; Weichman, Katie E. (Journal of Reconstructive Microsurgery, 2018)
Background Venous thromboembolism (VTE) is a significant cause of postoperative morbidity and a focus of patient safety initiatives. Despite giving appropriate prophylaxis in accordance with the Caprini risk assessment model, we observed a high incidence of VTE in patients undergoing microsurgical breast reconstruction at our institution. To explore factors contributing to these events, we compared patients undergoing microsurgical breast reconstruction who sustained postoperative VTEs to those who did not.Methods A retrospective review of all patients who underwent microsurgical free flap breast reconstruction at Montefiore Medical Center from January 2009 to January 2016 was conducted. Patients were divided into two cohorts; those sustaining postoperative VTE and those who did not. Patients were compared based on demographics, comorbidities, operative time, estimated intraoperative blood loss, need for transfusion, volume of transfusion, and discharge on postoperative aspirin.Results A total of 133 patients underwent microsurgical breast reconstruction during the study period. Nine patients (6.8%) had postoperative VTE and there was one (0.8%) death. Patients having VTE were more likely to be Hispanic (33.3%, n = 3) in the VTE group versus 8.1% (n = 6) in the control group (p = 0.011), more likely to have an increased mean transfusion volume (455.5 ± 367.8 vs. 139.51 ± 221.7 mL, p = 0.03), and were more likely to be discharged without aspirin (77.8%, n = 7 and 58.1%, n = 72; p = 0.003).Conclusion Patients sustaining postoperative VTE after microsurgical breast reconstruction are more likely to have an increased volume of blood transfusions and lack of discharge on postoperative aspirin.
Keywords: breast reconstruction; venous thromboembolism; microsurgery